Effect of Seasonality for Optimization of Germ Cell Extraction from Mature Blue Catfish. (10th February 2023) - Hettiarachchi, Darshika Udari; Alston, Veronica N.; Gurbatow, Jeremy; Hess, Hana N.; Su, Baofeng; Johnson, Andrew; Coogan, Michael P.; Wang, Jinhai; Xing, De; Li, Shangjia; Creamer, David; Zadmajid, Vahid; et al.
Abstract: Xenogenesis is an innovative tool for hybrid catfish (female Channel Catfish Ictalurus punctatus × male Blue Catfish I. furcatus ) seed production, accomplished by transplanting undifferentiated germ cells derived from a donor diploid fish into a sterile recipient, which then enables recipient fish to produce donor‐derived gametes. There is potential to collect donor‐derived germ cells from mature fish during certain times of the year depending upon seasonal temperature and serum sex steroid hormonal fluctuations. The objective of this study was to evaluate seasonal variations in germ cell counts and serum sex steroid hormonal profiles in mature Blue Catfish. Mature fish were collected monthly over the full annual cycle to quantify the number of live germ cells (spermatogonia A, oogonia), viability of germ cells, and levels of serum sex steroid hormones, including testosterone, 11‐ketotestosterone, and 17β estradiol. Extracted spermatogonia A counts were highest from April to June, whereas a significant decline was detected from July to November. Extracted live oogonia counts were highest in April and gradually decreased to zero over the months of May to August. Seasonal variations in serum testosterone, 11‐ketotestosterone, and 17β estradiol followed a similar pattern as the live spermatogonia A and oogonia counts. Even though spermatogonia A counts were relatively lower in mature than in immature Blue Catfish males, extracting spermatogonia A from mature Blue Catfish males during April to June provides an added advantage to the process of artificial fertilization, as it is required to sacrifice these fish to collect sperm.